2011
DOI: 10.1017/s0007114511002194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oligofructose on appetite profile, glucagon-like peptide 1 and peptide YY3-36 concentrations and energy intake

Abstract: In rats, oligofructose has been shown to stimulate satiety hormone secretion, reduce energy intake and promote weight loss. The present study aimed to examine the effect of oligofructose supplementation on appetite profiles, satiety hormone concentrations and energy intake in human subjects. A total of thirty-one healthy subjects (ten men and twenty-one women) aged 28 (SEM 3) years with a BMI of 24·8 (SEM 0·3) kg/m 2 were included in a randomised double-blind, cross-over study. The subjects received 10 g oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 21 publications
4
75
2
1
Order By: Relevance
“…To date, there have been no studies directly compared the effect of oligofructose on energy regulation with an inert dietary fiber. Indeed, in previous studies oligofructose has been compared to maltodextrin, an absorbable carbohydrate as a control (5,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been no studies directly compared the effect of oligofructose on energy regulation with an inert dietary fiber. Indeed, in previous studies oligofructose has been compared to maltodextrin, an absorbable carbohydrate as a control (5,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that soy protein and whey protein products enhance satiety [47,48] which may reduce energy intake [49]. Moreover evidence suggests that the consumption of fructan such as oligofructose is associated with lowered subjective hunger ratings and tendency to increases the concentration of satiety hormones [50]. Based on the nutritional ingredients of both formula diets it would be expected that HC as well as HP formula diet have the same satiating effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence exists that prebiotic effects on gut peptide release and appetite might be dose-dependent. In a crossover study carried out in adults receiving a supplement of either 10 or 16 g of OFS versus placebo for 13 days, a significant effect of OFS on energy intake and gut PYY and GLP-1 responses appeared only with the 16-g dose (Verhoef et al 2011).…”
Section: Gut Microbiota and Satietymentioning
confidence: 99%